2010
DOI: 10.1002/jmv.21716
|View full text |Cite
|
Sign up to set email alerts
|

Association of candidate susceptible loci with chronic infection with hepatitis B virus in a Chinese population

Abstract: A number of genetic loci have been proposed to be associated with persistent hepatitis B virus (HBV) infection. This study aimed to evaluate the association and interaction of susceptible genes with HBV persistence in a Chinese population. A total of 17 polymorphisms in 9 candidate genes were studied in 361 Chinese chronic hepatitis B patients and 304 patients who recovered spontaneously. Distributions of susceptible polymorphisms were examined in healthy Chinese and Caucasian populations. Gene-gene interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
(52 reference statements)
3
31
0
Order By: Relevance
“…These contradictory results could be partly explained by the extreme complexity in the cytokine network related to the intricate interactions of cytokines by which they induce or suppress their own synthesis or that of other cytokines, and antagonize or synergize with each other in many different and often redundant ways. On the other hand, it is now obvious that interactions between host genetic polymorphisms should be taken into account in defining complex and multifactorial disease risk, such as hepatitis C. Although the risk attributed to an individual polymorphism is often very small, it has been repeatedly demonstrated that a combination of specific genotypes may be a more significant and powerful approach in predicting disease risk [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…These contradictory results could be partly explained by the extreme complexity in the cytokine network related to the intricate interactions of cytokines by which they induce or suppress their own synthesis or that of other cytokines, and antagonize or synergize with each other in many different and often redundant ways. On the other hand, it is now obvious that interactions between host genetic polymorphisms should be taken into account in defining complex and multifactorial disease risk, such as hepatitis C. Although the risk attributed to an individual polymorphism is often very small, it has been repeatedly demonstrated that a combination of specific genotypes may be a more significant and powerful approach in predicting disease risk [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the frequency of the risk allele MCP-1 -2518G was much higher in Asians than in the Caucasian population (Chen et al, 2010). This discrepancy might be the result of distinct ethnicity-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some genes and loci, such as those encoding the Major Histocompatibility Antigens (HLA) [5,6], mannosebinding lectin/protein (MBP/MBL) [7,8], tumor necrosis factor (TNF) [9,10], natural resistance associated macrophage protein 1/ solute carrier family 11, member 1 (NRAMP1/SLC11A1) [11], vitamin D receptor (VDR) [12] and haptoglobin [13], control susceptibility to a variety of pathogens. Others, such as erythrocyte protein 3 (SLC4A1) [14], have been described as controlling susceptibility to only a single disease [15].…”
Section: Genes and Loci That Control Susceptibility To Human Infectiomentioning
confidence: 99%
“…Coding changes in two of the genes in this locus, type I IFN receptor gene, IFN-AR2, and the IL-10RB gene that encodes a receptor chain for IL-10-related cytokines including the IFN-lambdas, are associated with viral clearance [28]. Weak effects were reported for the HLA [6] and TNFA [10] genes, and the effect of mutation in MBP (mannose-binding protein) / MBL (mannosebinding lectin) gene was observed only in certain populations [8].…”
Section: Hepatitis Bmentioning
confidence: 99%